The new world history : a field guide for teachers and researchers - Dunn, Ross E.; Mitchell, Laura Jane, 1963-; Ward, Kerry (California world history library, 2016)
"The New World History is a comprehensive volume of essays selected to enrich world history teaching and scholarship in this rapidly expanding field. The forty-four articles in this book take stock of the history, evolving literature, and current trajectories of new world history. These essays, together with the editors' introductions to thematic chapters, encourage educators and students to reflect critically on the development of the field and to explore concepts, approaches, and insights valuable to their own work. The selections are organized in ten chapters that survey the history of the movement, the seminal ideas of founding thinkers and today's practitioners, changing concepts of world historical space and time, comparative methods, environmental history, the "big history" movement, globalization, debates over the meaning of Western power, and ongoing questions about the intellectual premises and assumptions that have shaped the field"--Provided by publisher